Relationship between sustainability and efficiencyin ovine production systems: Relación entre la sostenibilidad y la eficiencia en sistemas de producción ovina - Morantes, Martiña; Palomares, Rafaela Dios; Rivas, José; Alcaide-López de Pablo, David; García, Antón (Revista Científica de la Facultad de Ciencias Veterinarias, 2019)
The aim of this research was evaluating the relationship between the sustainability and the technical efficiency in sheep production systems in Castilla-La Mancha, Spain. The technical efficiency was estimated applying the stochastic frontier methodology, and sustainability through synthetic indexes through the MESMIS Framework. The relationship between sustainability and technical efficiency was analyzed through a truncated regression model with bootstrap technique. The degree of intensification of the sheep systems studied was variable, with a high dependence on external feeding, where the economic results are higher than those obtained in other investigations. The average technical efficiency was 0.74, with a range of 0.28 to 0.94, indicating that there is a wide margin of improvement of improvement of efficiency of the sector. The analysis of the relationship between sustainability and efficiency indicates a negative and highly significant effect of self-management, probably because associationism is not generating the expected results. While, that productivity had a positive effect on efficiency (P < 0.01).